2014
DOI: 10.7717/peerj.508
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing may facilitate professional interactions with inspectees during environmental inspections and enforcement conversations

Abstract: In the present work inspectors used Motivational Interviewing (MI) to promote environmentally sustainable behaviour in inspectees. MI is a counselling method with scientific support for various health behaviour changes. Inspectors (n = 32) in four Swedish municipalities received training in MI over a yearlong period. Their MI competency as well as their experience of using MI in routine inspections was monitored over the year. The results showed that inspectors significantly increased their competence in the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…However, several gaps in the literature remain. First, whereas the assessment of empathy by means of independent observers aligns with most previous research in the context of MI applications (e.g., Catley et al, 2006 ; Tollison et al, 2008 ; Forsberg et al, 2014 ), this approach tends to neglect the actual perspective of the change recipients. In other words, change recipients should be best suited to evaluate whether their interactional partner has confronted them or demonstrated empathic understanding.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, several gaps in the literature remain. First, whereas the assessment of empathy by means of independent observers aligns with most previous research in the context of MI applications (e.g., Catley et al, 2006 ; Tollison et al, 2008 ; Forsberg et al, 2014 ), this approach tends to neglect the actual perspective of the change recipients. In other words, change recipients should be best suited to evaluate whether their interactional partner has confronted them or demonstrated empathic understanding.…”
Section: Introductionmentioning
confidence: 83%
“…For example, Klonek and Kauffeld (2015) suggest that human resources departments could provide MI training for energy managers in order to reduce organizational energy consumption. In support of this argument, Forsberg et al (2014) showed that MI training increased the conversational skills of Swedish environmental inspectors. Furthermore, the authors showed that MI training positively affected inspectors’ empathy (rated by external observers).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Traditionally, MI is taught within the helping professions, for example, among therapists, counselors, physicians, or nurses (Madson et al, 2009 ; Forsberg et al, 2010 ; de Roten et al, 2013 ). More recent studies have provided evidence that MI is also teachable to non-helping professions, e.g., for engineers (Klonek and Kauffeld, in press ) or for environmental inspectors (Forsberg et al, 2014 ). Whereas MI has not been used in organizations in order to reduce energy-related behavior at work, it has great promise of equipping energy managers successfully with the right mindset and verbal skills in order to discuss these matters.…”
Section: What Is Motivational Interviewing and How Might It Improve Imentioning
confidence: 99%
“…More recent studies have provided evidence that MI is also teachable to non-helping professions, e.g., for engineers (Klonek and Kauffeld, in press) or for environmental inspectors (Forsberg et al, 2014). Whereas MI has not been used in organizations in order to reduce energy-related behavior at work, it has great promise of equipping energy managers successfully with the right mindset and verbal skills in order to discuss these matters.…”
Section: What Is Motivational Interviewing and How Might It Improve Imentioning
confidence: 99%